The effect of digital stories prepared according to realistic mathematics education on students' mathematical achievements, anxiety and attitudes - Ersin Çopur; Songül Tümkaya (Ömer Gökhan Ulum, 2024)
This research examined the effects of digital stories prepared according to Realistic Mathematics Education (RME) on the mathematics achievement, anxiety and attitudes of 4th-grade students. A quasi-experimental design with the pretest-posttest control group, one of the quantitative research designs, was used in the research. The research was conducted with 69 fourth-grade students studying in a public primary school in the Tarsus district of Mersin province in the second term of the 2021-2022 academic year. In the experimental group, the teaching was carried out by the researcher using digital stories prepared according to RME, the researcher carried out the learning in one of the control groups according to the current curriculum, and the classroom teacher carried out the teaching in the other control group according to the current curriculum for seven weeks. Two-factor ANOVA (mixed ANOVA) was used for mixed measurements to analyse the data obtained from the study. As a result of the statistical analyses, it was determined that digital stories prepared according to RME made a significant difference in the increase of students' academic achievement and mathematics attitudes but did not create a substantial difference in mathematics anxiety.